Pendidikan Musik Pondok Pesantren: Analisis Identitas Budaya Musik Hadroh Di SMA Jannatul Naim Internasional Collage - Eka Ria Nonita Putri; Riyan Hidayatullah (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Educational institutions today face a major challenge in balancing standards of religious identity and cultural roots. This study aims to analyze the pesantren-based learning model at Jannatul Naim International College (JaNIC), which integrates Hadroh music as a tool to strengthen students’ sense of identity and character. Using a qualitative approach, the study explores how Hadroh is not merely an extracurricular activity but a medium for transforming spiritual, disciplinary, and social values. Data collection was conducted through observation, interviews, and documentation to obtain a comprehensive picture of the learning process and the implementation of pesantren values in Hadroh activities. The results of the analysis indicate that Hadroh learning is able to bridge formal education with pesantren-based learning through the continuous internalization of religious and cultural values. This study argues that cultural identity within the Islamic boarding school educational model successfully creates harmony between global perspectives and local wisdom, shaping a generation that is modern yet remains true to its cultural identity. Furthermore, Hadroh activities also contribute to enhancing students’ sense of responsibility, cooperation, and social awareness in their daily lives.